Unequally spaced lateral bracings on compression flanges of steel girders. (August 2015) - Mehri, Hassan; Crocetti, Roberto; Gustafsson, Per Johan
Abstract: In the bridge sector, lateral bracings can be provided e.g. in the form of metal decks or horizontal truss bracings. Those bracings are more efficient at the regions of maximum lateral shear deformations generated from destabilizing forces of compression flanges e.g. near to the twisting supports. A model is presented in this paper, which relates the lateral buckling length of compression flange of steel girders to their lateral torsional buckling moment and can be used to investigate stiffness requirement of lateral bracings applied on the compression flanges between the twisting restraints. Analytical solutions were derived for the effects of bracing locations and bracing stiffness values on buckling length of compression flanges. Moreover, an exact and a simplified solution for the effect of rotational restraint of shorter-spans on critical load value of the compression members with unequally spanned lateral bracings were derived. The model can be suitable for design engineers to preliminary size the cross-section of beams and lateral bracings. Highlights: A simplified expression for critical moment of laterally braced girders is derived. Solutions for rotational restraint of unequal spans between bracings are derived. Applicability of the approach is examined by one comprehensive example. Approach enables choosing more proper location and stiffness of lateral bracings. Results verify that the approach can be very useful in pre-design stage.